Scrutinizing the Impact of Family Economic Status on Students' Academic Achievement - Bhandari, Ram Bahadur; Timsina, Tatwa Prasad (International Research Journal of MMC, 2024)
A chief objective of this article is to scrutinize the impact of family economic status on the students' academic achievement. Children’s academic success is a multifaceted outcome influenced by various factors, and family economic status is one of the significant determinants. The study synthesizes existing literature to provide a comprehensive understanding of how socioeconomic factors shape students' educational courses. This article has been based on the cross-sectional survey design which employed the socio-economic status as an independent variable the students’ academic achievement as a dependent variable. Data were collected through the survey questionnaire from 386 students who were studying at 14 high schools situated in Makawanpur district, Nepal. Linear regression analysis was conducted to examine the impact of family economic status on the students' academic achievement. The regression analysis (R-Square: .647) which is known as a predictive analysis depicted that 64.7% change in the students’ academic achievement was due to the family economic status, and remaining 35.3% change was due to others factors. Studying the impact of family economic status on students' academic achievement is crucial for understanding and addressing the potential inequalities and challenges that may arise in educational outcomes. Such a study allows for targeted interventions and support to improve overall educational equity. The impact of family economic status on students' academic achievement is multifaceted. It encompasses resource access, school quality, socioemotional well-being, and parental involvement. Acknowledging these dynamics is crucial for educators, policymakers, and researchers in developing interventions to bridge achievement gaps and promote equal opportunities for all students, irrespective of their family's economic background.